Legal Challenges in Regulating Cryptocurrency: A Global Comparative Analysis - Clara Mendes; Rafaela Lima; Jamil Khan; Harly Chifford Jonas Salmon (Rechtsnormen: Journal of Law, 2026)
Background. Growing adoption of cryptocurrencies has generated significant legal concerns related to asset classification, consumer protection, anti-money laundering compliance, taxation, financial stability, and cross-border enforcement. Regulatory responses vary considerably across jurisdictions, creating legal uncertainty and challenges for governments, businesses, and investors. Purpose. This study aims to analyze the principal legal challenges in cryptocurrency regulation and compare regulatory approaches adopted by different jurisdictions worldwide. Method. A qualitative comparative legal research design was employed, utilizing doctrinal analysis of legislation, regulatory frameworks, policy documents, judicial decisions, and institutional reports from selected jurisdictions, including the United States, the European Union, China, Japan, Singapore, and El Salvador. Results. The findings reveal substantial regulatory fragmentation driven by differences in legal traditions, policy priorities, and institutional capacities. Legal classification ambiguity, anti-money laundering compliance, cross-border enforcement difficulties, consumer protection concerns, and adaptation to technological innovation emerged as the most significant regulatory challenges. Jurisdictions implementing balanced and adaptive regulatory frameworks demonstrated greater regulatory certainty and market stability than those adopting highly restrictive or excessively permissive approaches.   Conclusion. The study concludes that effective cryptocurrency governance requires regulatory clarity, risk-based supervision, and enhanced international cooperation to address the evolving complexities of digital asset markets while supporting innovation and financial integrity.